Dyslipidaemia associated with the highly active antiretroviral therapy in aids patient: reversion after switching (stavudine to tenofovir and lopinavir/ritonavir to atazanavir/ritonavir) - Domingos,Hamilton (2007)
Antiretroviral therapy has been associated with hyperlipidemia in AIDS patients. This case illustrates the classic metabolic effects associated to the HAART including protease inhibitors and/or stavudine. It was showed that the management of the HAART-associated dyslipidaemia with conventional antihyperlipidemic therapy may fail, being the switching strategy the best option.